Layanan Konseling Berbasis Komunitas Bagi Klien di Balai Rehabilitasi Sosial - Nur Azizah (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2019)
The beneficiaries or Persons with Social Welfare Problems (PMKS) at the Social Rehabilitation Center cannot be separated from problems that arise both from before and during their stay or undergoing rehabilitation. Therefore counseling is expected to be one of the services that can be provided to help beneficiaries with various problems. their respective characteristics. This study uses a qualitative approach with a descriptive type of research to find out the Counseling Service Model at Beneficiaries at the Social Rehabilitation Center (Ex-Residency District of Banyumas). This research was conducted at the